2018
DOI: 10.1007/s40299-018-0390-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Stress-Coping Abilities on Stress in Practicum Training

Abstract: Practicum is a highly stressful situation whereby trainee teachers are subjected to a highquality standard, deals with numerous students' behaviour, adapt with the school climate and so forth. In this study, stress-coping factors comprising self-efficacy, subjective wellbeing and emotional intelligence experienced by 137 trainee teachers in the Sabah Teacher Education Institutions (TEIs) are associated with practicum stress. Resiliency Scale for Young Adults (RSYA), Teachers' Sense of Efficacy Scale, the Emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Some scholars have proven [2,49,51] that university students state that they need social support because of increased stress levels. In retrospect, this shows the correlation between an individual's emotional wellness and emotional intelligence.…”
Section: A Theoretical Model For Examinationmentioning
confidence: 99%
“…Some scholars have proven [2,49,51] that university students state that they need social support because of increased stress levels. In retrospect, this shows the correlation between an individual's emotional wellness and emotional intelligence.…”
Section: A Theoretical Model For Examinationmentioning
confidence: 99%
“…3. The mean score of workability laboratories conventional [15,35,37]. Students are satisfied with their project laboratory work, they acquire the skills needed to face the challenges of their future profession.…”
Section: Scientific Work Skillmentioning
confidence: 99%
“…Thus, these studies operationalize and measure stress as the psychological experience of stress and lack of coping during a specified period of time, but without attaching this to specific events or factors in the learning environment (i.e., perceived stress). For example, Ngui and Lay [10,11] found that field-practice-related perceived stress among student teachers was predicted by self-efficacy and subjective wellbeing. Geng, Midford, and Buckworth [12] found that the practicum-related perceived stress levels were significantly correlated with the time spent by student teachers on planning for teaching, so the more hours spent on planning, the less stress.…”
Section: Environmental and Perceived Stress In Field Practice Placementsmentioning
confidence: 99%
“…While a number of different measures of perceived stress have been used in the previously mentioned research, a significant number of the identified quantitative studies of student teachers' perceived stress as related to field practice appear to have utilized the 10-item version of the perceived stress scale (PSS-10; [21]), for example, Geng and Midford [14] and Ngui and Lay [10]. The PSS-10 has also been utilized in numerous studies on the perceived stress of student teachers in relation to the campus or university parts of their education (e.g., [15,22]).…”
Section: The Measurement Of Perceived Stress In Teacher Education Fie...mentioning
confidence: 99%